Can you track down Bigfoot? : an interactive monster hunt - Terrell, Brandon, 1978-2021 (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2022)
In this plot-your-own story book, the reader who wants to be a monster hunter follows the clues to find Bigfoot, or a Yeti, or the Florida Skunk Ape.
About your adventure -- Sightings! -- The fog of Washington -- The Skunk Ape of the Everglades -- The Himalayan Yeti -- Bigfoot: real or hoax?
41 choices, 20 endings--Front cover.
Includes bibliographical references (page 111) and index.
3-6
620L
S
4.6
Keywords: Sasquatch -- Juvenile fiction; Yeti -- Juvenile fiction; Monsters -- Juvenile fiction; Plot-your-own stories; Sasquatch -- Fiction; Yeti -- Fiction; Monsters -- Fiction; Monster fiction; Choose-your-own stories